Analysis of Multiple‐choice Propositions in Secondary School English Tests - Kang, Yongbo (Journal of Theory and Practice of Social Science, 2023)
Multiple choice questions are a common question type used in current secondary school English tests. Multiple choice questions can test students' completion of multiple learning tasks such as vocabulary, grammar, and listening. Multiple choice questions have the advantages of effectively testing students' learning ability, wide coverage, convenient and efficient use, etc., and occupy an important position in daily secondary school English tests. To this end, this study will analyze the proposition system of multiple‐choice questions in the current secondary school English test, make use of the strengths and avoid the weaknesses, and provide design principles and recommendation for the proposition system.